Theorizing feminist research in rural areas of the Punjab, Pakistan - Choudhry, Abubakar Nazeer; Abdul Mutalib, Rozita; Ismail, Nur Syakiran Akmal (2019)
This paper constructed on former work by the authors and on the succeeding literature. It argues that a feminist research provides a powerful tool in assisting us to understand women’s lives, their experiences, their concerns based on gender discrimination.This paper seek for empowerment and liberation of women by conceptualizing and thinking about the findings of feminist researchs which are often applied to promote social changes and social justice for women.The paper begins by outlining why the theorization of term ‘feminist methodology’ is used to tag an ideal approach for conducting feminist research which reveals that the basic premise of feminist theory is that women have been excluded from traditional philosophy. In Pakistan, especially in Punjab, women inferior and subordinated status is in practice, including women’s political deprived affiliation to contest election and cast the vote. Such circumstances tend to make them less empowered.In addition, the relational analyses of liberal feminism and ethnographic structure of the Punjabi society shows a strong correlation that justifies the position of researchers to select a liberal feminist theory as a theoretical framework.The only way to bring changes in such traditional societies are gradual process of reforms. So, strategies of liberal feminists can be more successful as reformists rather than radicals, socialists and Marxists.